1. 3ax - 6ay+ bx - 2by

2. 4px - 4py - 3qx + 3qy

3. mx + nx - my - ny

4. lm (5x - 1) + 3pq (5x -1)

1. 3ax - 6ay+ bx - 2by = 3a(x-2y)+b(x-2y) = (x-2y)(3a+b)

2. 4px - 4py - 3qx + 3qy= 4p(x-y)-3q(x-y) = (x-y)(4p-3q)

3. mx + nx - my – ny= x(m+n)-y(m+n) = (m+n)(x-y)

4. lm (5x - 1) + 3pq (5x -1)= (5x-1)(lm+3pq)

explain number 1

in the first two terms 3a is common factor so 3a (x-2y)

In the last two terms b is acommon factor so b(x-2y)

In both (x-2y) is common factor. We are left with (3a+b)

so (x-2y)(3a+b)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up